PERIOPERATIVE OUTCOMES OF COMBINED HEART SURGERY AND LUNG TUMOR RESECTION : A SYSTEMATIC REVIEW - Atin, Fulgensius; P. Sintoro, Henry; Valerie Gunawan, Alyssa Claudia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Cancer and cardiovascular disease are the leading causes of death in both men and women worldwide. There are concerns regarding the potentially increased mortality and complication rates of simultaneous surgery and the adequacy of lung exposure during heart surgery. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of cthe requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 14 articles, whereas the results of our search on SagePub brought up 91 articles. The results of the search conducted for the last year of 2013 yielded a total 9 articles for PubMed and 23 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, combined heart surgery and lung tumor resection had a low mortality rate and an acceptable complication rate. Subgroup analyses revealed that most patients with lung cancer underwent uncompromised anatomical resection and mediastinal lymph node sampling or dissection during combined cardiothoracic surgery, and showed off-pump CABG may reduce the complication rate compared with on-pump CABG. Further researches are still needed to verify these findings.